Aprendizagem e psicodinâmica organizacional - Motta, Fernando C. Prestes (2003)
This study aims at investigating the current theories on Organization Learning, elaborating a critical study about this concept and its evolution. This study will further investigate the linkages between thew post-industrial paradigm and the learning organization concept, using the Institutional Theory na overarching approach.